Unveiling ‘HEREDIAQUA’: An Exploration of Association Picture Storytelling in Documentary Filmmaking - Markadi, Bhimo Wicaksono; Swandi, I Wayan; Udayana, Anak Agung Gde Bagus (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
This study explores the application of the “association picture story” genre in documentary filmmaking, particularly focusing on the film “Herediaqua,” to effectively communicate water sustainability issues. The research employs a three-stage methodology: exploration (field research, observation, interviews, and collection of visual materials), experimentation (applying association picture story techniques in short film formats and testing with audiences), and creation (synthesizing findings to produce a cohesive and impactful film).Results indicate that “Herediaqua” successfully uses strong visual symbolism and narrative to convey messages about the interconnectedness between humans and nature, effectively enhancing audience awareness and understanding of water sustainability issues. The film employs powerful visual language to communicate its environmental message, evoking emotional responses from viewers. Positive audience feedback confirms the film’s success in communicating its message, demonstrating the effectiveness of the association picture story technique in visual narration. The conclusion asserts that the “association picture story” technique is a powerful tool for conveying environmental messages through visual storytelling. “Herediaqua” serves not only as a viewing experience but also as an educational medium and a catalyst for inspiring environmental conservation efforts. By leveraging compelling visual narration and engaging storytelling, the film promotes awareness and encourages concrete actions for sustaining the planet’s life. This research contributes to advancing documentary filmmaking by highlighting the effectiveness of combining visual symbolism with strong narrative techniques.